Effects of short-term spinal cord stimulation on patients with prolonged disorder of consciousness: A pilot study - Zhuang, Yutong; Yang, Yi; Xu, Long; Chen, Xueling; Geng, Xiaoli; Zhao, Jizong; He, Jianghong (Frontiers in Neurology, 2022)
Background: spinal cord stimulation (SCS) can improve the level of awareness of prolonged disorder of consciousness (pDOC), but its application is restricted due to damage of invasive operation. Short-term spinal cord stimulation (st-SCS) in a minimally invasive manner will better balance the benefits and risks. Objectives: This study focuses on the safety and efficacy of st-SCS for pDOC and reveals the modulation characteristics of different frequencies of SCS. Methods: 31 patients received 2-week st-SCS treatment and 3-months follow-up. All patients were divided into two types of frequency treatment groups of 5 Hz and 70 Hz according to the postoperative electroencephalography (EEG) test. The efficacy was assessed based on the revised coma recovery scale (CRS-R). Results: The results showed a significant increase in CRS-R scores after treatment (Z=-3.668, p<0.001) without significant adverse effects . Univariate analysis showed that the minimally conscious state minus (MCS-) benefits most from treatment. Furthermore, two frequency have a difference in the time-point of the CRS-R score increase. 5 Hz mainly showed a significant increase in CRS-R score at 2 weeks of treatment (p=0.027), and 70 Hz additionally showed a delayed effect of a continued significant increase at 1 week after treatment (p=0.004). Conclusion: st-SCS was safe and effective in improving patients with pDOC levels of consciousness, and was most effective for MCS-. Both 5 Hz and 70 Hz st-SCS can promote consciousness recovery, with 70 Hz showing a delayed effect in particular.